Pendampingan Remaja dan Orang Tua dalam Meningkatkan Kualitas Baca Al-Qur'an (Studi Kasus di Mushola Al-Jannah Dukuh Krajan Desa Bedrug Kecamatan Pulung Ponorogo) - Hamdan Afandi; Teguh Ansori (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This activity was carried out in Dukuh Krajan, Bedrug Village, Pulung District, Ponorogo Regency. Al-Qur'an is the holy book of Muslims which serves as a guide for humans in directing their lives. In understanding the reading of the Koran there are several methods, one of which is the sorogan method. The sorogan method is an individual method where students come to the teacher to study the book and the teacher guides them face to face or face to face (face to face). In fact, the sorogan method has existed since ancient times and we still encounter it today in learning to read the Koran in Indonesian society. Using the Asset Based Community Development (ABCD) method, this research can be carried out by direct interviews. how important is the role of parents in guiding their children when educating faith and piety and providing education in the field of religion.